2010
DOI: 10.4021/jocmr2010.03.275w
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Tumour of the Breast: Carcinosarcoma

Abstract: Carcinosarcoma of the breast, also known as metaplastic carcinoma, is rare with very few cases reported in the literature. A 46-year old female patient presented with a mass in her left breast. Physical examination, ultrasonography and mammography findings were consistent with malignancy. The mass was totally removed. Histopathological examination revealed carcinosarcoma of the breast. Histologic grade of the tumour was III. Ki67 proliferation index was found 40% positive. Tumour cells were positive for p53 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 11 publications
(12 reference statements)
1
25
0
3
Order By: Relevance
“…In another study, the 5-year survival rates for stage 1, 2, 3 and 4 were reported as 73%, 59%, 44% and 0%, respectively (37). In our series, the 36-month disease-free survival rate was 52.5% (±18.6), and the overall survival rate was 71.1% (±18).…”
Section: Discussionsupporting
confidence: 49%
“…In another study, the 5-year survival rates for stage 1, 2, 3 and 4 were reported as 73%, 59%, 44% and 0%, respectively (37). In our series, the 36-month disease-free survival rate was 52.5% (±18.6), and the overall survival rate was 71.1% (±18).…”
Section: Discussionsupporting
confidence: 49%
“…Reports of both women and female dogs have used the criteria of the Nottingham grading system to evaluate only the epithelial component of these biphasic tumors (a term also used for tumors with proliferation of both epithelial and mesenchymal components; 16,36). Other studies with strictly mesenchymal malignant tumors adopted certain precepts to evaluate the differentiation of sarcomatous proliferation.…”
Section: Cssmentioning
confidence: 99%
“…No entanto, há um consenso geral de que o tratamento inicial deve ser cirúrgico, com preferência pela mastectomia radical 12 . Apesar de o acometimento ganglionar ser mais raro nessa afecção, ele é maior em 10 a 20% em relação aos sarcomas, conforme mencionado, sendo a pesquisa do linfonodo sentinela uma opção para diminuir a morbidade da linfonodectomia axilar 5 .…”
Section: Discussionunclassified